2011
DOI: 10.1167/iovs.11-8120
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Properties of UV Filter Molecules of the Human Eye

Abstract: With aging, the ratio primary/secondary UV filters in the human lens decreases from approximately 10:1 to 2:1. The obtained results demonstrate that the quality of the secondary UV filters is inferior compared to the primary ones, which may result in a higher susceptibility of old lenses to UV light. That might be an important factor for the development of the age-related cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Eqn (2) holds as long as the pseudo-first-order triplet energy transfer reaction is much faster than the second-order triplet annihilation reaction, and the efficiency of triplet KNA formation in the acetone-sensitized photolysis is close to 100%. 35 The laser pulse energy dependence of the A and B parameters shown in Fig. 8B exhibits a deviation from linear dependence which takes place at laser intensities above 0.5 mJ per pulse.…”
Section: 35mentioning
confidence: 86%
See 3 more Smart Citations
“…Eqn (2) holds as long as the pseudo-first-order triplet energy transfer reaction is much faster than the second-order triplet annihilation reaction, and the efficiency of triplet KNA formation in the acetone-sensitized photolysis is close to 100%. 35 The laser pulse energy dependence of the A and B parameters shown in Fig. 8B exhibits a deviation from linear dependence which takes place at laser intensities above 0.5 mJ per pulse.…”
Section: 35mentioning
confidence: 86%
“…The early excited-state dynamics of KNY is similar to that of KN. 1 It has been shown that excitation of KN and other UV filters results in a charge transfer from the amino to the carbonyl group; 35 very likely that the same charge transfer occurs during the KNY excitation, which is supported by a large Stokes shift of the fluorescence band relative to the absorption spectrum (Fig. 1).…”
Section: Photophysics and Photochemistry Of Knymentioning
confidence: 93%
See 2 more Smart Citations
“…4-Aryl-4-oxobut-2-enoic acids (also considered as β-aroylacrylic acids), their derivatives represent an important class of compounds with wide spectrum of biological activities including antibacterial activity [1][2][3][4][5], anti-ulcer and cytoprotective properties [6,7], kynurenine-3-hydroxylase [8] and antiproliferative activity toward Human cervix carcinoma (HeLa) [9,10]. Moreover, the β-aroylacrylic acids have been attracting increasing attention in view of their high reactivity as building blocks for the synthesis of wide variety of compounds of various classes due to their selective transformations with different reagents.…”
Section: Introductionmentioning
confidence: 99%